Coagulation removal of Sb(V) from textile wastewater matrix with enhanced strategy: Comparison study and mechanism analysis. (December 2019) - Liu, Yuanli; Lou, Zimo; Yang, Kunlun; Wang, Zheni; Zhou, Chuchen; Li, Yizhou; Cao, Zhen; Xu, Xinhua
Abstract: The wide use of antimony in textile industry has posed threat to ecological health and attracted increased attention. The objective of this work was to develop enhanced coagulation strategies including PFS/FeSO4 and aerated PFS/FeSO4 for efficient antimony elimination from textile wastewater matrix. With a dosage of 0.75 mM Fe, aerated PFS/FeSO4 coagulation could achieve 82.6% removal of 500 μg L −1 Sb(V) from simulated textile wastewater, which was better than PFS (77.6%) and PFS/FeSO4 coagulation (79.9%). Compared with PFS and PFS/FeSO4 coagulation, aerated PFS/FeSO4 strategy could meet the indirect discharge standard (<100 μg L −1 ), without any other additional treatment. pH ranged from 5 to 6 could reach 93.8% Sb(V) removal, by affecting coagulant hydrolysis and charges on flocs. Phosphate ion with a level more than 0.03 mM could compete with Sb(V) species and thus reduced its removal. Temperature of 35 °C could lead to enhanced Sb(V) removal by accelerating coagulant hydrolysis. Flocs of aerated PFS/FeSO4 had smaller average size than that of PFS and PFS/FeSO4 coagulation. FeOOH was the hydrolysis product of aerated PFS/FeSO4 strategy. Adsorption, rather than direct and co-precipitation was predominant in the coagulation mechanism. From the phosphate extraction test, 64% of the Sb could form inner-sphere surface complex during aerated PFS/FeSO4 coagulation removal. Graphical abstract: Image 1 Highlights: Aerated PFS/FeSO4 was the optimum strategy for Sb(V) coagulation. The Sb(V) after aerated PFS/FeSO4 coagulation was under the discharge standard. The Sb (V) removal efficiency was significantly affected by pH and phosphate. Adsorption played an important role in aerated PFS/FeSO4 coagulation for Sb(V).